Prediction of superhard carbon allotropes from the segment combination method - He, Ch.; Sun, L.Z.; Zhong, J. (Сверхтвердые материалы, 2012)
Many superhard allotropes of carbon have been proposed in recent years for the purpose of explaining the superhard carbon phases observed in the processes of cold compressing graphite and carbon nanotubes. In this paper, we have reviewed recent advances in searching for superhard phases of carbon from a segment combination view and found that they can be divided into two groups: (i) combinations of segments from cubic diamond and hexagonal diamond with 5-6-7 carbon rings and (ii) combinations of segments from hexagonal diamond and mutated hexagonal diamond with 4-6-8 carbon rings. Finally, an additional example of extending these allotropes of carbon to their corresponding boron nitride counterparts has been discussed.